Extension project Caix'adentro: report on the virtual teaching of stage lighting in the UNIFAP's Theater Graduation Course (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
This report presents the development process of an online and interactive teaching material for theater teaching in basic education, which is being carried out as an extension action of the Licentiate Course in Theater at the Federal University of Amapá. During the process, the focus of the material in development turned to the contents of scenic lighting, seeking to create a 3D virtual environment that simulates reality and that makes it possible to experiment with various creative possibilities in the field of lighting. As the project, is still under development, this text will present some assumptions that are guiding the construction, as well as some partial results obtained.
Keywords: teaching material; didactic design; virtual environment; scenic lighting